Men and women’s prisons in the Portuguese press: the gender of punishment - Cervantes Saavedra, Luisa de (Punishment & society, 2019)
Since prison life is out of common people’s sight, the media have a particularly important role in legitimating or, conversely, de-legitimating public discourses and policies about punishment, incarceration and rehabilitation. In the present study, our analysis was grounded in 83 news, 55 of these about men prisons, 24 about women prisons and 4 news about public policies in general, although having specificities about men’s and women’s prisons published in a Portuguese national newspaper between 2005 and 2014. The analysis suggests that, with very few exceptions, gender is an important issue in the media construction for men's and women's prisons and male and female inmates; gender norms of masculinity and femininity are essentialized, justifying different practices of control in prison policies. Dangerous, violent, resistant and manipulative male inmates call for prison policies based on risk control and managerialism, whereas docile and reliable female inmates call for policies grounded on rehabilitation but also security. Apart from this representation, our analysis also shows that the news, in general, tends to align with a reformist approach, failing to interrogate the wider role of imprisonment in social control or to discuss its alternatives.